A brief war dictionary - Adamsen, Johannes (Futures of Education, Culture and Nature - Learning to Become, 2024)
The essay, A Brief War Dictionary, explores the nuanced and often contradictory language surrounding war, conflict, and peace. Through a series of reflective and incisive entries, the author examines terms such as "civilians," "genocide," and "education," revealing how language shapes perceptions, ideologies, and narratives of war. The work interrogates the ethical implications of terms used in war discourse and critiques the impact of ideological rigidity and propaganda. Additionally, it highlights human dignity and the role of education as a counterbalance to the divisiveness of war, advocating for intercultural understanding and dialogue. This thought-provoking essay challenges readers to consider the intersection of language, ideology, and humanity in the context of modern conflicts.